ANALISIS EMPIRIK MULTIMEDIA INTERAKTIF PEMBELAJARAN FISIKA MENGGUNAKAN LECTORA INSPIRE PADA MATERI CAHAYA DI SMP - Suci Rahma Utari; Muhammad Nor; Muhammad Nasir (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to analize the interactive multimedia in physics learning empirically. The approach used in this study is research and development (R&D) with instructional design model, ADDIE. Data were collected through the questionnaires. Respondents of this research were from teachers and students, teacher as an expert user while student as a user. The data of instrument were analyzed using product moment SPSS and Ms. Excel. The highest validity score of each teacher as expert and student as user is 0,821 & 0,776 while the reliability score each is 0,955 & 0,906. The results of this research indicate that the interactive multimedia is valid and reliable.Key Words: Empirical Analysis, Interactive Multimedia, Lectora Inspire, ADDIE, Validity test, Reliability test